Commented translation of the tale Cagliuso, by Giambattista Basile - Tommasello Ramos, Maria Celeste [UNESP]; De Jesus Reis, Adriana Aparecida [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2019)
In this work, we present the translation in Portuguese of a children version of the tale Cagliuso, by the writer Giambattista Basile (1575-1632), which may be the source-text of the tale Puss on Boots, by Charles Perrault. The translation is introduced by explanations about the author and his work, commentary in notes, and followed by the original text in standard Italian.
Keywords: Annotated translation; Giambattista Basile; Italian Literature; Tale; Translation